Analysis Of Rice Availability In Central Java Province 2018-2022 - Wati, Bela Christiana; Faridatussalam, Sitti Retno (Jurnal Ilmu Manajemen Profitability, 2024)
Central Java Province, as one of the regions with the largest population in Indonesia, has large resource potential in the food sector, especially in rice crops. Food, as the main human need, is the key to maintaining a region's food security. This research uses a quantitative approach with secondary time series and cross section data from January 2018 to December 2022, involving 29 districts and 6 cities in Central Java Province. Factors influencing rice availability were analyzed using the panel data method. The panel data method with the Fixed Effect Model (FEM) was chosen as the best model, showing that rice production and population have a positive and significant influence on the availability of rice in Central Java Province. Meanwhile, rice harvest area and rice productivity did not have a significant effect. The research results show that rice production has a positive effect on rice availability, but rice availability is also influenced by population size. The ever-increasing population puts pressure on the availability of rice, because the greater the population, the greater the need for rice consumption. These findings contribute to the efforts of the government and farming business actors in maintaining food security in Central Java Province